2020
DOI: 10.12688/f1000research.25753.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of touch-screen technology usage on hand skills among preschool children: a case-control study

Abstract: Background: Little is known on how time spent on touch-screen technology affects the hand skills development of preschool children. This study aimed to investigate the effects of touch-screen technology usage on hand skills among preschool children. Methods: Case-control design was employed to compare the hand skills of children who were engaged in touch-screen technology. A total of 128 participants aged between five and six years old who attended preschool were recruited and divided into two groups: high usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Research on motor skills has predominantly focused on children, examining the development and refinement of these skills from early childhood ( 32 , 33 ). Our study probes the connection between socioeconomic factors, measured through ADI and cognitive status among middle-aged adults living in AZ.…”
Section: Discussionmentioning
confidence: 99%
“…Research on motor skills has predominantly focused on children, examining the development and refinement of these skills from early childhood ( 32 , 33 ). Our study probes the connection between socioeconomic factors, measured through ADI and cognitive status among middle-aged adults living in AZ.…”
Section: Discussionmentioning
confidence: 99%
“…Teknologi interaktif menjadi isu karena perkembangan motorik bergantung pada pengalaman motorik anak. (Daud et al, 2020) Media pembelajaran saat ini sudah dapat diakses pada gawai-gawai berbasis android seperti smartphone. Penelitian ini bertujuan mengungkapkan kehadiran media pembelajaran berbasis gim dan gawai android mampu membuat perbedaan terhadap hasil belajar pengembangan karakter nilai agama dan moral pada anak usia dini dibanding kelas konvensional.…”
Section: Pendahuluanunclassified
“…A study that examined the relationship between screen time and language development showed that children who watched more than two hours of television per day had higher probabilities of having poor communication and language skills without parental or other career guidance (9). Additionally, early exposure to screens was linked to poor development of social and emotional, cognitive, linguistic abilities and hand skills, as well as other talents (10,11). A child's growth is crucial and fast in the early years of life.…”
Section: Introductionmentioning
confidence: 99%